Answer:
y =8.7
Step-by-step explanation:
y + 8.5 = 17.2
Subtract 8.5 from each side
y +8.5 -8.5 = 17.2 -8.5
y =8.7
Answer:
(x+1)(x-1)(x+3)(x-3)
Step-by-step explanation:
x4-10x^2+9
Group expression so that the coefficients of the x^2 terms add up to +9.
= x^4 -9x^2 - x^2+9
match coefficients in both groups
= x^4 -9x^2 - (x^2-9)
factor each group
= x^2 (x^2-9) - 1(x^2-9)
now factor out the common factor (x^2-9)
= (x^2-1)(x^2-9)
Finally, factor each quadratic factor
= (x+1)(x-1)(x+3)(x-3)
Answer:
https://www.khanacademy.org/math/cc-sixth-grade-math/cc-6th-data-statistics/dot-plot/v/frequency-tables-and-dot-plots
Step-by-step explanation:
Answer:
-17-17,-17,-17,-14,-14,-14,-14,6,6,6,6
Step-by-step explanation:
hope it helped.
A. 35% decrease yearly
B. 267.75
C. How much the computer is worth after 4 years